2020
DOI: 10.1186/s13071-020-3983-9
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of larval competition and exposure to permethrin for the development of the rodent malaria Plasmodium berghei in the mosquito Anopheles gambiae

Abstract: Background: Mosquitoes and other vectors are often exposed to sublethal doses of insecticides. Larvae can be exposed to the runoff of agricultural use, and adults can be irritated by insecticides used against them and move away before they have picked up a lethal dose. This sublethal exposure may affect the success of control of insectborne diseases, for it may affect the competence of insects to transmit parasites, in particular if the insects are undernourished. Methods: We assessed how exposure of larvae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…While most insects are declining 2 , many mosquito species are thriving 3 , 4 . Recent laboratory and mesocosm studies provided important clues suggesting that anthropogenic disturbances can promote population growth of several pathogen-transmitting mosquito species, or disease vectors 5 - 8 , and potentially mediate interactions between mosquito species 9 , their hosts 10 , their pathogens 11 , 12 , and their predators 13 . This hints that, if these patterns hold true for natural systems, the way humans influence their local environment presents a critical driver of disease risk 14 .…”
Section: Introductionmentioning
confidence: 99%
“…While most insects are declining 2 , many mosquito species are thriving 3 , 4 . Recent laboratory and mesocosm studies provided important clues suggesting that anthropogenic disturbances can promote population growth of several pathogen-transmitting mosquito species, or disease vectors 5 - 8 , and potentially mediate interactions between mosquito species 9 , their hosts 10 , their pathogens 11 , 12 , and their predators 13 . This hints that, if these patterns hold true for natural systems, the way humans influence their local environment presents a critical driver of disease risk 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that the adaptation of anopheline vectors to polluted water can influence adult emergence times 28 – 30 . Similarly, exposure to sub-lethal doses of insecticides has been reported to increase the life span of infected mosquitoes 31 . In the current study, we found that presence of the sesquiterpene lactone parthenin released from the root exudate of P. hysterophorus to the oviposition site environment influenced mosquito bionomics.…”
Section: Discussionmentioning
confidence: 97%
“…The sublethal exposure to permethrin at larvae or adults of An. gambiae reduced the infection prevalence by Plasmodium berghei [94]. These studies with laboratory-consolidated models pointed that the level of interference of the exposure of the larvae to insecticides in the process of infection of mosquitoes depends on the species of both vector and pathogen and the mode of action of the compounds.…”
Section: Sublethal Exposure Of Larvae To Insecticidesmentioning
confidence: 96%
“…Studies have been carried out considering the interaction between adult mosquitoes derived from exposed larvae and malaria-causing parasites [86,87,94]. For instance, the exposure of Culex pipiens to the neonicotinoid imidacloprid did not affect the life history traits of individuals nor the susceptibility of adults to infection by avian malaria parasite (Plasmodium gallinaceum) [86].…”
Section: Sublethal Exposure Of Larvae To Insecticidesmentioning
confidence: 99%